CTF meeting 2012: Translation of the basic understanding of the biology and genetics of NF1, NF2, and schwannomatosis toward the development of effective therapies. Issue 3 (17th January 2014) - Widemann, Brigitte C.; Acosta, Maria T.; Ammoun, Sylvia; Belzberg, Allan J.; Bernards, Andre; Blakeley, Jaishri; Bretscher, Antony; Cichowski, Karen; Clapp, D. Wade; Dombi, Eva; Evans, Gareth D.; Ferner, Rosalie; et al.
<x xml:space="preserve">Abstract</x> The neurofibromatoses (NF) are autosomal dominant genetic disorders that encompass the rare diseases NF1, NF2, and schwannomatosis. The NFs affect more people worldwide than Duchenne muscular dystrophy and Huntington's disease combined. NF1 and NF2 are caused by mutations of known tumor suppressor genes (NF1 and NF2, respectively). For schwannomatosis, although mutations in SMARCB1 were identified in a subpopulation of schwannomatosis patients, additional causative gene mutations are still to be discovered. Individuals with NF1 may demonstrate manifestations in multiple organ systems, including tumors of the nervous system, learning disabilities, and physical disfigurement. NF2 ultimately can cause deafness, cranial nerve deficits, and additional severe morbidities caused by tumors of the nervous system. Unmanageable pain is a key finding in patients with schwannomatosis. Although today there is no marketed treatment for NF‐related tumors, a significant number of clinical trials have become available. In addition, significant preclinical efforts have led to a more rational selection of potential drug candidates for NF trials. An important element in fueling this progress is the sharing of knowledge. For over 20 years the Children's Tumor Foundation has convened an annual NF Conference, bringing together NF professionals to share novel findings, ideas, and build collaborations. The 2012 NF Conference held in New Orleans hosted over 350 NF researchers and clinicians. This article provides a synthesis of the highlights presented at the conference and as such, is a "state‐of‐the‐field" for NF research in 2012. © 2014 Wiley Periodicals, Inc.